Populasi Lychas mucronatus (Scorpiones:Buthidae) di Kampus Undip Tembalang Semarang. - Rohman, Arief Fatkhu; Hadi, Mochamad -; Tarwotjo, Udi - (Bioma : Berkala Ilmiah Biologi, 2010)
Scorpion is an animal that has a high adaptability in various environmental conditions. Lychas mucronatus isone species of scorpion of the Buthidae family, which can be found on Campus Diponegoro University, SemarangTembalang. No data population and the spread of L. mucronatus on the campus of Diponegoro University, SemarangTembalang. This study aims to assess the population of L. mucronatus on the campus of Diponegoro University,Semarang Tembalang. This research was conducted in October-November 2009 in the region Undip TembalangHyderabad campus. Samples were taken by hand collecting techniques directly in the field accompanied by an imagecapture scorpion on its habitat. L. population data mucronatus were analyzed descriptively. The results showed L.mucronatus found on campus Undip Tembalang were 22 specimens consisting of 15 females, 2 males, 1 juvenile,and 4 specimens of unknown gender. L. mucronatus females in this study more likely in because of male mortalityduring mating season. L. mucronatus was found in grassland and shrub habitats, fields, and around the tree, L.mucronatus occupy four types of microhabitat characteristics, namely: leaf litter, rotten wood, in the soil, and understones. L. mucronatus most common in grassland and shrub habitats with sloping contour with microhabitat under arock. The presence of predators and competitors are likely to be a factor not found in L. mucronatus in severallocations on campus Undip Tembalang.